2007
DOI: 10.1111/j.1440-1754.2007.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the management of neonatal hyperglycaemia in Australasia

Abstract: There is a wide variation in the management of neonatal hyperglycaemia between tertiary neonatal units in Australasia. This reflects the paucity of data available in this area. Further research on the management of neonatal hyperglycaemia is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…The model-based controller was trialled in simulation with targets of 4 mmol/L, 5 mmol/L, 6 mmol/L, 7 mmol/L and 8 mmol/L, which represents a range of target glucose concentrations likely to be encountered in neonatal critical care [37].…”
Section: Controller Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The model-based controller was trialled in simulation with targets of 4 mmol/L, 5 mmol/L, 6 mmol/L, 7 mmol/L and 8 mmol/L, which represents a range of target glucose concentrations likely to be encountered in neonatal critical care [37].…”
Section: Controller Developmentmentioning
confidence: 99%
“…Similarly, Alsweiler et al [37] demonstrated a wide range of responses from different clinical units when questioned on glycaemic control targets. Hence, a control system needs to handle different glucose targets to comply with local practices.…”
Section: Introductionmentioning
confidence: 95%
“…Elevated blood glucose levels (BG) (Hyperglycaemia) is a common complication of prematurity and stress in neonatal intensive care, and while definitions and thresholds vary [11], studies show that 30-70% of very/extremely low birth weight infants have at least one BG> 8 mmol/L [12][13][14][15][16]. Hyperglycaemia is associated with increased mortality [15][16][17], and morbidity/complications in this cohort [15][16][17][18][19][20][21], but there is still debate over whether hyperglycaemia causes increased morbidity, or is reflective of worsened condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moderately elevated blood glucose levels are recently more tolerated or recommended [63] because of the fear of hypoglycemia and higher nursing effort frequently associated with TGC [64]. A recent study by Alsweiler and colleagues [65] found that while all surveyed neonatal units would consider use of insulin for hyperglycemia, the threshold for commencing insulin infusions varied, as well as the choice of glycemic management using altered dextrose infusion rates. Most units reported little to no hypoglycemia, and these findings agreed with previous surveys that found a lack of consensus on the management of neonatal hyperglycemia, possibly reflecting the lack of data available in this area [65].…”
Section: Discussionmentioning
confidence: 99%